2014
DOI: 10.2118/160876-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure for Measuring Contact Angles When Surfactants Reduce the Interfacial Tension and Cause Oil Droplets to Spread

Abstract: Viscoelastic surfactants (VESs) are used as diverting agents in carbonate matrix acidizing. However, these surfactants can adversely affect the wettability around the wellbore.Receding contact angles were measured with the conventional method to study the effect of spent-acid solutions with an amphoteric amine-oxide VES and the mutual solvent ethylene glycol monobutyl ether (EGMBE) on the wettability of Austin cream chalk rocks. The conventional method involves the injection of oil droplets into the surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This is also reflected in VES flooding; the rock wettability may alter significantly for the swept area, which was continuously flushed by VES solution. The water wetness is significantly enhanced, which may be particularly noticeable in the near-wellbore zone [27]. The possible mechanism for a higher adsorption of VES is shown in Figure 8.…”
Section: Dynamic Agingmentioning
confidence: 98%
See 1 more Smart Citation
“…This is also reflected in VES flooding; the rock wettability may alter significantly for the swept area, which was continuously flushed by VES solution. The water wetness is significantly enhanced, which may be particularly noticeable in the near-wellbore zone [27]. The possible mechanism for a higher adsorption of VES is shown in Figure 8.…”
Section: Dynamic Agingmentioning
confidence: 98%
“…It can yield additional oil recovery of 20-25% after water flooding [24][25][26]. It was also demonstrated that a VES solution can alter the wettability of rock [27]. VES has different adsorption characteristics in different rock mineral components [28], but the effect on rock wettability is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Angle (θ) created at the contact line of the liquid-fluid interface and the solid substrate is typically used to calculate the contact angle [24]. In applications involving oil recovery, the contact angle of a droplet of water or oil is measured for a rock surface that has already been treated with the substance anticipated to have an impact on the wettability [25][26][27]. The experimental steps were as follows and shown in Figure 1: 1.…”
Section: Contact Angle Measurementmentioning
confidence: 99%